FOSSIL WOOD OF PSEUDOTSUGOXYLON GEN. ET SP. NOV. (PINACEAE) FROM THE PLIOCENE OF THE SOUTHERN PRIMORSKII REGION - Blokhina N.I.; Bondarenko O.V. (My University, 2004)
A new form genus, Pseudotsugoxylon, is designated to include fossil woods with anatomical characters typical of extant Pseudotsuga. The material came from the Pliocene of the Pavlovka lignite field (southern Primorskii region). A new species, Pseudotsugoxylon pavlovskiense, which shows a very close similarity to the extant North American species Pseudotsuga menziesii and P. macrocarpa, is described.
Keywords: Pseudotsugoxylon; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен